Factors influencing personal saving in Malaysia / Norehan Nordin (Faculty of Business and Management, 2008)
Personal saving is the portion of personal income that is left over after personal current taxes and outlays for personal consumption expenditures, non mortgage interest payments, and net current transfers to government and the rest of the world. It excludes capital gains because capital gains represent changes in the prices of assets that are already owned, not unspent portions of income receipts. Personal saving represents the contribution from persons to national saving, which is the total amount that is available to fund investment in fixed assets, inventories, or foreign assets. This paper empirically analyzes the Factors Influencing Personal Saving in Malaysia. This paper is concentrated on Personal Saving data, total return on KLCI and household consumption expenditure. The study used multiple regression analysis to see the relationship between dependant and independent variables. Personal saving is used as dependant variable and stock return, home ownership and disposable income as independent variables. As a conclusion stock return and home ownership could accept null hypotheses and disposable income can reject the null hypotheses. The most consistent result is that disposable income positively and significantly influences Malaysian personal savings. Also, the interactive processes of Multiple Regression Analysis, disposable income significantly explain personal savings.